PERAN GURU DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS IV YANG BERKEBUTUHAN KHUSUS DI SDN 04 PALEMBANG - Putri Sintiya; Erfan Ramadhani; Aldora Pratama (JGK (Jurnal Guru Kita), 2023)
The Role of The Teacher in Learning Indonesian Language in Class IV Students with Special Needs at SDN 04 Palembang. The role of the teacher is not only to educate and teach, but the role of the teacher also guides and directs normal students in general and students with special needs without any differences. Based on this, the problem in this research is how the role of the teacher in learning Indonesian in grade IV students with special needs (autism) at SDN 04 Palembang. The purpose of this study was to find out how the role of the teacher in learning Indonesian in grade IV students with special needs (autism) at SDN 04 Palembang. The method used in this research is descriptive qualitative research method. The data collected by the researchers were observation, interviews and documentation. Data analysis uses data reduction, data presentation and conclusion drawing. The results of this study were through the observation of one of the students with special needs at SDN 04 Palembang and interviews with the fourth grade teacher and obtained the results that the teacher's role was very influential in the planning, implementation and evaluation stages in the Indonesian language learning process for one of the students with special needs. In the learning process the teacher uses simple methods, strategies and media which are averaged out with normal students without any difference because these students are in public schools not special schools (SLB). The teacher also has difficulty delivering material and has difficulty evaluating one of the students with special needs. The teacher's role is not only educating and teaching, but the teacher's role is also to guide and direct and provide motivation, enthusiasm and approach to one of the students who experience problems with special needs and normal students.